ADULT EDUCATION MANAGEMENT IN PORTO AND CATALONIA: A CASE STUDY - Christian Muleka Mwewa; Ana Inés Renta Davids; Abudo Machude (Universidade Federal de Sergipe, 2018)
The purpose of this study was to analyze the organizational structure and educational methods of two training centers, namely the Professional School of Minho (Portugal) and the Association for Social and Occupational Promotion (Spain). Data collection included daily observation of and participation in the "departments" of adult education and training in both centers. We argue that training in these institutional contexts is based upon a permanent dialogue between learners' home experiences and learning opportunities that allow them to acquire new professional, cultural, political and social skills. Therefore, the training process in these centers becomes a movement between prior knowledge and new experiences. This process is observed in the dialogue between learners, instructors, context and everyone involved in the educational process.